A general model for simulating the quench behavior of canted-cosine-theta (CCT) quadrupole magnets. (December 2022) - Kang, Rui; Wang, Yingzhe; Yang, Huan; Zhou, Jin; Chen, Xin; Feng, Ao; Li, Wei; Ma, Rui; Shi, Jinrui; Wang, Menglin; Hou, Zhilong; Wang, Chengtao; et al.
Highlights: A multi-physics model, which involves an electrical circuit module and a heat transfer module as well as their coupling, is established to simulate the quench-back effect in a CCT quadrupole magnet. The difference of quench integrals between the calculated and measured values are less than 5%. This model is easily reproducible and could be applied to CCT magnets with different configurations. At the nominal operating condition of the studied magnet, the quench-back effect could reduce the quench integral by more than 2/3, strongly releasing the difficulty of quench protection and leaving potential for further increase the current density of the CCT magnet. Abstract: Quench-back is a complex but fascinating effect that could occur in canted-cosine-theta (CCT) magnets: the fast discharge after quench of the superconducting coil induces significant eddy currents in the conductive coil formers and then the eddy current evenly heats up the whole coil, accelerating the current decay in the coil without increasing its terminal voltage. In this study, we introduce a multi-physics model, which involves an electrical circuit module and a heat transfer module as well as their coupling, to simulate the quench behavior in a CCT quadrupole magnet with special attention on the quench-back effect. The simulation is found to reproduce the measured current decay of a CCT quadrupole magnet well, with less than 5% deviation in the quench integrals at different quench currents. Under the nominal operating condition of the studied coil, the quench-back effect reduces the quench integral by more than two-thirds, strongly releasing the difficulty of quench protection. Accurate simulation of the quench-back effect would allow it to be fully utilized in magnet design, and eventually allows higher operating current density in CCT magnets.